1933 Haw. Sess. Laws 38, § 6 - (:unkn) unknown (My University, 1933)
An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 6: Prohibited individuals convicted of violent crimes from owning, possessing, or having under their control a pistol, revolver, or ammunition.
Keywords: POSSESSION - DANGEROUS PERSONS